Fast MRI of RF Heating Via Phase Difference Mapping - Shapiro, Erik M. (2002)
A method is presented for the rapid acquisition of temperature maps derived from phase difference maps. The temperature-dependent chemical shift coefficients (TDCSCs) of various concentrations of aqueous cobalt and dysprosium-based compounds were measured. The largest TDCSC calculated was for 100 mM DyEDTA, which had a TDCSC of −0.09 PPM/K; 160 mM CoCl(2) had a TDCSC of −0.04 PPM/K. These temperature-dependent chemical shifts (TDCSs) result in phase changes in the MR signal with changing temperature. Agarose phantoms were constructed with each paramagnetic metal. A fast gradientecho (FGRE) MR image was acquired to serve as the baseline image. A “test” MRI procedure was then performed on the phantom. Immediately afterwards, a second FGRE MR image was acquired, serving as the probing image. Proper image processing as a phase difference map between the probing image and the baseline image resulted in an image which quantitatively described the temperature increase of the phantom in response to a particular “test” imaging experiment. Applications of this technique in assessing the safety of pulse sequences and MR coils are discussed.